Multiple myeloma: five-year experience at a University Hospital - Todaro,Juliana (2011)
Objective: To present a descriptive analysis of patients diagnosed with multiple myeloma, correlating it with mortality. Methods: A retrospective study that analyzed consecutive patients diagnosed with multiple myeloma under follow-up at the Faculdade de Medicina do ABC from 2006 to 2010. Results: The median age was 58.5 years. Anemia was observed upon diagnosis in 87% of patients, hypercalcemia in 38%, and creatinine levels higher than 2 mg/dL in 19%. M protein was detected in 85.7%. The five-year survival rate was 74.6%. Multivariate analysis showed statistical significance for Durie-Salmon staging (p = 0.037). The International Staging System and immunoglobulin type did not correlate significantly with survival of the group. Conclusion: This set of cases from a tertiary public healthcare service reflect the approach of multiple myeloma in a predominantly young population with advanced clinical staging, with results comparable to those of the literature.